Analyse von Kundenaktivitäten und der Bereitstellungsqualität von Büchern aus Kundensicht Mit einer Untersuchung von Kundenkommentaren zu Mietangeboten für E-Books - Wittrock, Janina (HTWK Leipzig - OA-Hochschulverlag, 2019)
"This master thesis explores service characteristics that are relevant for book readers when they evaluate a service as well as starting points for providers when they plan to optimize their services from a customer's point of view. In the first part ways of accessing books (buying, borrowing, rent) and the reading behavior of Germans will be described. Then the concept "quality of provision" of books will be discussed which distinguishes five quality dimensions of a service: diversity of content and arranging of books, basic technology (printed book or digital environment), temporal and spatial access, costs of access and ease of use. By using secondary material for each dimension individual quality characteristics will be identified. Next the theoretical background of the activity theory and a special way of thinking, the customer-dominant-logic, from the Nordic school will be explained briefly. Based on this a set of consumer activities related to books will be presented and some activities that are relevant for the work will be described in more detail by means of secondary material (reading books, choosing books, organizing books and information). Further customization and personalization will be proposed as strategies for individualization of services and their function for consumers will be explained. The secondary data used in the work comes from empirical data out of consumer surveys in libraries and bookshops, nationally representative surveys and from results of academic research from different fields. In the final part of this thesis an own data collection will be conducted by using a content analysis of consumer comments of two e-book rental apps (n = 1,245 comments). The analysis should clarify, if the quality characteristics, the book-related activities and the strategies for individualization described before can be found in everyday reality of consumers. After that the results of the content analysis will be presented. Finally the major findings will be summarized and connected to the research questions."